Intraoral slow-releasing polymeric patches containing sodium fluoride and chlorhexidine: Development and evaluation - Yarmunja Mahabala Karuna, Swati Pralhad, Srinivas Mutalik, Anupama P. Nayak, Bharath Singh Padya (Journal of Applied Pharmaceutical Science, 2020)
Early childhood caries (ECC) has been considered to be at epidemic proportions in developing countries. There is a scientific consensus regarding the benefit of a constant supply of low levels of fluoride, especially at the biofilm/saliva/ tooth interface in preventing dental caries. The use of controlled and sustained delivery systems containing fluoride can be considered as an effective means of eradicating ECC in high-risk individuals. The use of chlorhexidine as an antimicrobial agent in combination with fluoride is beneficial (Naidu et al., 2016). Slow-releasing devices containing both fluoride and chlorhexidine do not exist as of now. Hence, the aim of the present study was to design a slow-release polymeric intraoral patch containing fluoride and chlorhexidine, and to evaluate the amount of medicament released over 20 days. Three slow-releasing patches were fabricated with different concentrations of gelatin to determine the maximum release of medicaments. Using in-vitro drug release studies it was observed that, out of three patches prepared with equal concentrations of chlorhexidine (80 mg) and sodium fluoride (288 mg), a patch I containing 1,000 mg of gelatin was found to be beneficial for a sustained release of both medicaments.
Keywords: Early childhood caries, chlorhexidine, sodium fluoride, slow release of drug, primary teeth.